Childrens speech disorders (Classifications-causes-treatment) “Analytical Sociological study” (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
Speech disorder in children is a common problem nowadays. Its causes can be attributed to either an organic impairment resulting from a genetic factor or a specific incident, or it may be caused by difficulties in academic learning or language acquisition errors from the surrounding environment. Therefore, the objective of this study was to identify the causes of speech and language expressive disorders in children, which can be physiological, psychological, or social in nature. Additionally, the study aims to recognize the classifications of speech disorders in children, such as omission, substitution, addition, and distortion. Furthermore, the study focuses on understanding the treatment methods and mitigating the problem. In cases where the cause of speech disorders is learning difficulties rather than an organic impairment, early intervention and treatment can be provided through specialized childcare centers with portage programs. When beginning treatment under the supervision of a specialized team, cooperation between the family and the centers is crucial to achieve the desired outcome and equip these children with the necessary skills to eventually integrate them into school. The sociological analysis tool was used to explain and analyze these factors, along with the appropriate descriptive and analytical approach for this research.